Trajectory generation of differentially flat systems - Morillo Piña, Atilio (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The aim of this work is to develop a method for trajectory generation of nonlinear control systems with the property of differential flatness. This property allows to reduce the problem of generating dynamically constrained trajectories in the state space, into the simpler problem of constructing curves constrained to satisfy some determined boundary conditions in the flat output space. The general problem have been restricted to the case of systems that can be transformed into a linear controllable system, via state feedback, as these systems enjoy a differential flatness property of O order and may be suitably handled by using well known algorithms.